ATIM-17. PEMBROLIZUMAB BLOCKS PD-1 ON CAR T CELLS ADMINISTERED INTRAVENTRICULARLY TO GLIOBLASTOMA PATIENTS. (5th November 2018) - Portnow, Jana; Synold, Timothy; Tran, Vivi; Chiu, Vivian; Alizadeh, Darya; Wang, Dongrui; Brito, Alfonso; Kilpatrick, Julie; Mcnamara, Paige; Forman, Stephen; Badie, Behnam; Brown, Christine
Abstract: BACKGROUND: Checkpoint inhibitors have shown efficacy in other solid tumors and are being studied in glioblastoma. For patients treated with anti-PD-1 monoclonal antibodies, such as pembrolizumab, CSF concentrations and blockade of PD-1 on T cells present in the CSF have not been reported. Such information would provide valuable context for applying checkpoint inhibitors for the treatment of CNS malignancies. METHODS: CSF and blood samples were obtained from 6 glioblastoma CAR T cell study patients who received intraventricularly administered CAR T cells. These patients were also treated with pembrolizumab 200 mg intravenously every 3 weeks. Pembrolizumab levels in CSF and blood were measured using an ELISA assay. FACS analysis for PD-1 blockade was performed on endogenous and CAR T cells detected in CSF samples, and the results were compared to cells in CSF without pembrolizumab treatment. RESULTS: Data analyzed from 3 patients samples so far show that average pembrolizumab levels in the CSF and serum were 330 ± 114 ng/mL and 64 ± 8 µg/mL, respectively. The average CSF/serum ratio was 0.5 ± 0.1%. In 1 patient from whom multiple CSF/blood samples were obtained over 3 months, steady-state CSF levels ranged from 155–394 ng/mL throughout each 21 day cycle of pembrolizumab. PD-1 was completely blocked on both endogenous T cells as well as CAR T cells that were delivered directly into the CSF. CONCLUSIONS: To our knowledge, this is the first report of pembrolizumab concentrations in the CSF after intravenous administration. CSF levels were 0.5% of serum concentrations and remained stable throughout a 21 day cycle of pembrolizumab. PD-1 was found to be blocked on endogenous T cells in the CSF. Furthermore, even though they were relatively low, pembrolizumab levels in the CSF were sufficient to block PD-1 on intraventricularly administered CAR T cells.